Out of the shadows - Singleton, Sarah, 1966- (Clarion Books, 2008)
In 1586 England, Elizabeth, whose family is hiding a Catholic priest from Protestant reformers, and Isabella, a girl of her own age who was similarly sheltered by "faery" folk 300 years earlier when Catholics accused Isabella's mother of witchcraft, work together to keep the persecutors away.